PENGARUH BEBAN KERJA DAN LINGKUNGAN TERHADAP PRILAKU CYBERLOAFING KARYAWAN (Studi Kasus pada PT. Telkom Indonesia Witel Bengkulu) - Malindra, Afif Dwi Cahya; Yulinda, Ade Tiara (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
This study aims to determine the effect of workload and work environment on cyberloafing behavior of employees at PT Telkom Indonesia Witel Bengkulu. The independent variables in this study are workload (X1) and work environment (X2), while the dependent variable is cyberloafing (Y). This study uses a quantitative method with a multiple linear regression approach. Data were collected through questionnaires distributed to 50 respondents, and data analysis was carried out using SPSS. There are several data analysis techniques used in this study, including using multiple linear regression analysis, determinant coefficients, and also hypothesis testing. Based on the results of the study, it can be concluded that workload (X1) and work environment (X2) have a positive effect on cyberloafing behavior (Y). with the results of multiple linear regression analysis obtained the equation Y = 8.894 + 0.580 (X1) + 0.587 (X2) and the determination coefficient (R²) of 0.356 or 35.6%. Based on the hypothesis test, namely the t test (partial) and the f test (simultaneous) with the F-count value (12.983)> F-table (3.18) and the significance value (0.003) <0.05, then together these variables have a positive and significant effect on cyberloafing. Keywords: workload, work environment and employee cyberloafing